The N‐terminal D1 domain of Treponema pallidum flagellin binding to TLR5 is required but not sufficient in activation of TLR5. Issue 11 (7th September 2019) - Xu, Man; Xie, Yafeng; Tan, Manyi; Zheng, Kang; Xiao, Yongjian; Jiang, Chuanhao; Zhao, Feijun; Zeng, Tiebing; Wu, Yimou
Abstract: Syphilis is a chronic bacterial infection caused by Treponema pallidum ( T pallidum ) and the pathogenesis that T pallidum infection induces immunopathological damages in skin and other tissues remains unclear. We have previously reported that recombinant flagellins of T pallidum can elicit IL‐6 and IL‐8 transcriptions via TLR5 pathway. To identify the domains which induced the pro‐inflammatory activity and the importance of the interactions between TLR5 and domains, homology‐based modelling and comparative structural analyses revealed that Tp flagellins can combine with TLR5 directly. Deletion mutations showed that the ND1 domain binding to TLR5 is required but not sufficient in TLR5 activation. Moreover, site‐directed mutagenesis analysis indicated that the arginine residue ( Tp flagellins R89) of the ND1 domain and its adjacent residues ( Tp flagellins L93 and E113) constitute a hot spot that elicits IL‐6, IL‐8 transcriptions and TLR5 activation, and affects the binding of Tp flagellins to TLR5. Taken together, these results give insight into the pathogenesis of T pallidum and may contribute to the future design of Tp flagellins‐based therapeutics and syphilis vaccine.